Foreign Policy as Part of Strengthening the Polish Economy in the World: the Ethical Aspect - Pawlak, Mateusz (Annales. Etyka w Życiu Gospodarczym, 2014)
The technological, economic and political advances of the 20th and 21st centuries have established new conditions for the development of civilization. The world economy has simultaneously expanded (the number of states/organization participating in world trade or the volume of heterogeneous transactions) and shrunk (close interrelations between transactions, no matter their geographic origins). Economic policy has gained an indispensable role in the creation of order in international relations and foreign policy. The tendency to prioritize foreign policy aims towards economic policy aims has resulted in ‘reverse flow’, i.e. foreign policy has become a central part of national economic policy. The engagement of external action services and public budget in economic promotion and investments triggers (inter alia) the ethics dilemma. The mentioned ethical aspect is often omitted when discussing ‘the economic foreign policy’. For instance, the ethics dilemma can appear when development and humanitarian aid are taken into account or when it comes to assessing the results (and membership) of economic missions. In this context, the author analyses the Polish foreign policy example and attempts to answer two questions. First, are the economic activities performed by external action services effective? Second, are the mentioned activities in accordance with the social ethical code of conduct? The author focuses on three elements – development and humanitarian aid, the participation of Polish diplomats in economic promotion, and economic missions.